(3eLdS ef CeGdi GdMGaX CHj CMeO eYeQ Hf YHO GdhGMO Hf GdaGNQ GdbQTis - (3GHf GdebjQ , Ydj Hf GdMSjf Hf Ydj Hf efUhQ GdHZOGOj GdfLGQ, CHh GdMSf,J (B643 (3g` s
(3ChdgG (B:s
(3CNHQfG GdTjN CHh Gdfhf jhfS Hf EHQGgje SeYJ CHGfYje CMeO Hf YHO Gddg GdMGaX EedGkA YdjfG ef daXg jbhd (B: (3SCdJ QMec Gddg Yf MGd eMeO GdMGQK Hf CHj CSGeg s
(3BNQgG (B:s
(3ef TYQ CHj GdYJGgjI (B: (3YLHkG dGeQF jPd deNdhb hjcajI cd jhe QZja s
(3Jhai eYeQ Hf YHO GdhGMO SfI (B564s
(3cJHJ GdfSNI Hbde bdjd GdfbW HBNQgG bQGAI efbhdI ef GdCUd GdefJSN efg SfI (B559 (3hSeGYGJ CNQi SfI (B726s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B279s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3cJH HNWg GdYGde CMeO Hf YHO GdbGOQ GHf CMeO Hfs
Keywords: (3GdMOjK h GdeUWdMs